Attributes of High-Performing Small Practices in a Guideline Implementation: A Multiple-Case Study. (December 2020) - Nguyen, Ann M.; Cuthel, Allison M.; Rogers, Erin S.; Van Devanter, Nancy; Pham-Singer, Hang; Shih, Sarah; Berry, Carolyn A.; Shelley, Donna R.
Objective: HealthyHearts NYC was a stepped wedge randomized control trial that tested the effectiveness of practice facilitation on the adoption of cardiovascular disease guidelines in small primary care practices. The objective of this study was to identify was to identify attributes of small practices that signaled they would perform well in a practice facilitation intervention implementation. Methods: A mixed methods multiple-case study design was used. Six small practices were selected representing 3 variations in meeting the practice-level benchmark of >70% of hypertensive patients having controlled blood pressure. Inductive and deductive approaches were used to identify themes and assign case ratings. Cross-case rating comparison was used to identify attributes of high performing practices. Results: Our first key finding is that the high-performing and improved practices in our study looked and acted similarly during the intervention implementation. The second key finding is that 3 attributes emerged in our analysis of determinants of high performance in small practices: (1) advanced use of the EHR; (2) dedicated resources and commitment to quality improvement; and (3) actively engaged lead clinician and office manager. Conclusions: These attributes may be important determinants of high performance, indicating not only a small practice's capability to engage in an intervention but possibly also its readiness to change. We recommend developing tools to assess readiness to change, specifically for small primary care practices, which may help external agents, like practice facilitators, better translate intervention implementations to context.